2020
DOI: 10.1371/journal.pone.0234568
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of stroma fibers, microvessel density and immune cell populations determine overall survival in pancreatic cancer—An analysis of stromal morphology

Abstract: associated with reduced overall survival (27 months vs. 34 months, p = 0.039). In multivariable analysis, the combination of random orientation of stroma fibers and low microvessel density (HR 1.592, 95%CI 1.098-2.733, p = 0.029), high CD4/CD3 ratio (HR 2.044, 95%CI 1.203-3.508, p = 0.028) and high density of CD163 positive cells (HR 1.596, 95%CI 1.367-1.968, p = 0.036) remained independent prognostic factors. Conclusion Alignment of stroma fibers and microvessel density are simple histomorphological features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Therefore, PRO-C6 may be a measure of collagen alignment (anisotropy). Clinically, collagen fiber alignment is a negative prognostic factor in PDAC [12,77]. This might be due to the fact that fiber alignment promotes migration, by being highways for cancer cells to travel on, and furthermore, highly aligned fibers result in stiff tissue, which increases interstitial fluid pressure, resulting in reduced drug uptake and thereby treatment resistantcy [78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PRO-C6 may be a measure of collagen alignment (anisotropy). Clinically, collagen fiber alignment is a negative prognostic factor in PDAC [12,77]. This might be due to the fact that fiber alignment promotes migration, by being highways for cancer cells to travel on, and furthermore, highly aligned fibers result in stiff tissue, which increases interstitial fluid pressure, resulting in reduced drug uptake and thereby treatment resistantcy [78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the literature, which shows that high collagen fiber alignment specifically, rather than high collagen density, is a negative prognostic indicator in PDAC patients. [25,55] Here, remediation of desmoplasia by TPMIL + 690 nm (12.5 PDT dose product) is partially attributed to dose-dependent photochemical degradation of collagen. [18] At low PDT doses (<25 J cm −2 ), the stiffness of collagen hydrogels increases, likely due to collagen crosslinking.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with the literature, which shows that high collagen fiber alignment specifically, rather than high collagen density, is a negative prognostic indicator in PDAC patients. [ 25,55 ]…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that PaC is a hypovascular and hypoxic solid tumor, and PaC tissue frequently exhibits aberrant proliferation of human vascular endothelial cells (HUVECs) [50,51]. Moreover, it is reported that the microvessel density (MVD) in tumor tissue is positively correlated with the progression of PaC [52][53][54][55].…”
Section: Lncrna-uca1 Promotes the Tumor Angiogenesis In Pacmentioning
confidence: 99%